Perioperative management of opioid-tolerant chronic pain patients - Rozen, MD, Dima; DeGaetano, MD, Noah P. (Journal of Opioid Management, 2006)
Opioids occupy a position of unsurpassed clinical utility in the treatment of many types of painful conditions. In recent years there has been a noticeable shift regarding the use of opioids for the treatment of both benign and malignancy-related pain. As acceptance of the prescribing of opioids for chronically painful conditions has grown, many more opioid-tolerant patients are presenting for surgical procedures. It is therefore imperative that practicing anesthesiologists become familiar with currently available opioid formulations, including data regarding drug interactions and side effects, in order to better plan for patients’ perioperative anesthetic needs and management. Unfortunately, there is a lack of scientifically rigorous studies in this important area, and most information must be derived from anecdotal reports and the personal experience of anesthesiologists working in this field. In this review, we shall discuss current chronic pain management and the impact of opioid use and tolerance on perioperative anesthetic management.